FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PENGEMUDI TAKSI DI PERUSAHAAN X KOTA JAKARTA TIMUR TAHUN 2023 - Mujhijha Sulthon Batavia (2023)
Work fatigue is a problem that has a serious impact on companies and workers. Taxi drivers have busy working hours and are constantly dealing with heavy traffic, which makes them prone to burnout. This study aims to find factors associated with work fatigue in company X taxi drivers in East Jakarta in 2023. The research method used is quantitative analytic with a cross-sectional study design. The sample of this study consisted of 116 taxi driver companies X. This sample was obtained using simple random sampling. Chi-square test and Fisher Exact Test are used to determine the relationship between variables. The results show that the variables associated with work fatigue were age with a p-value (0.025), smoking habits with a p-value (0.019), work stress with a p-value (0.048) and workload with a p-value (0.036). While the variable that is not related to work fatigue is nutritional status with a p-value (1,000). Based on the results of the study it was concluded that there was a relationship between age, smoking habits, work stress and workload on work fatigue. Company X taxi drivers can reduce the risk of burnout by increasing time to rest, reducing workload, and reducing negative thoughts that can interfere with work.